Retrospective OSL Dosimetry With Common Pharmaceuticals and Food Supplements - Ekendahl, Daniela; Reimitz, Dan (Frontiers in Public Health, 2022)
Several common pharmaceuticals such as ibuprofen, paracetamol, aspirin, oral contraceptives, drugs for the prevention of motion sickness and food supplements such as table vitamins and minerals have been studied for the purposes of retrospective dosimetry using optically stimulated luminescence (OSL). The essence is that the tablets with these drug substances contain additive crystalline materials which, after irradiation and stimulation, may exhibit luminescence. For most of the pharmaceuticals and food supplements, a radiation-induced dose-dependent OSL signal was detected. Subsequently, basic dosimetric characteristics of the materials were studied, specifically sensitivity changes during repeated OSL readings, dose response, zero-dose, minimum detectable dose (MDD) and fading. The most radiation sensitive materials were food supplements with Mg providing zero-dose and MDD values at the level of several mGy. For Mg supplements, considerable sensitivity changes in OSL signal were observed. Despite this, they could be corrected using a Single-Aliquot Regenerative-dose (SAR) protocol. The OSL signals of the other materials were relatively weak but they were well reproducible and exhibited linear dose response. The MDD values were variable among the materials and ranged from 0.1 to several Gy. However, for some of the pharmaceuticals, a very high and variable zero-dose of more than 3 Gy was observed that would rule out the possibility of dose reconstruction for triage purposes. The OSL signal exhibited a significant fading rate for most of the materials. The measurements for dose reconstruction should be performed as soon as possible after irradiation, i.e. within a maximum of a few days.